Eleven Years of Data on the Jefferson Scale of Empathy-Medical Student Version (JSE-S): Proxy Norm Data and Tentative Cutoff Scores - Hojat, Mohammadreza (Med Princ Pract, 2015)
OBJECTIVE: This study was designed to provide typical descriptive statistics, score distributions and percentile ranks of the Jefferson Scale of Empathy-Medical Student version (JSE-S) of male and female medical school matriculants to serve as proxy norm data and tentative cutoff scores. SUBJECTS AND METHODS: The participants were 2,637 students (1,336 women and 1,301 men) who matriculated at Sidney Kimmel (formerly Jefferson) Medical College between 2002 and 2012, and completed the JSE at the beginning of medical school. Information extracted from descriptive statistics, score distributions and percentile ranks for male and female matriculants were used to develop proxy norm data and tentative cutoff scores. RESULTS: The score distributions of the JSE tended to be moderately skewed and platykurtic. Women obtained a significantly higher mean score (116.2 ± 9.7) than men (112.3 ± 10.8) on the JSE-S (t(2,635) = 9.9, p < 0.01). It was suggested that percentile ranks can be used as proxy norm data. The tentative cutoff score to identify low scorers was ≤95 for men and ≤100 for women. CONCLUSIONS: Our findings provide norm data and cutoff scores for admission decisions under certain conditions and for identifying students in need of enhancing their empathy.